A novel control strategy for the partial nitrification and anammox process (PN/A) of immobilized particles: Using salinity as a factor. (April 2020) - Liu, Chengcheng; Yu, Deshuang; Wang, Yanyan; Chen, Guanghui; Tang, Peng; Huang, Shuo
Graphical abstract: Highlights: Improved the mechanical strength and mass transfer performance of PVA-SA-immobilized particles by adding PEG. Investigated the effects of different salinities on the partial nitrification and anammox processes. Realized the stable operation of PN/A by adding salinity and performed genome-wide analysis on the changes in bacteria. Abstract: The impact of the addition of salinity on partial nitrification and anammox (PN/A) was investigated in this study. The sludge was immobilized by polyethylene glycol (PEG)-modified polyvinyl alcohol (PVA)-sodium alginate (SA) immobilization technology, and the effective diffusion coefficient ( De ) of the immobilized particles was measured to be 0.313 × 10 −9 m 2 ·s −1, indicating that the system has excellent mass transfer performance. An experiment was carried out by adding NaCl to create a salinity gradient. It was found that the initiation of partial nitrification was achieved at a concentration of 10 g·L −1 NaCl and the nitrite accumulation rate (NAR) reached 81.03%, which could provide sufficient NO2 − -N for subsequent anammox. Additionally, an anammox reactor operating at the same salinity maintained a stable state after acclimation, and the removal rates of NH4 + -N and NO2 − -N reached 80%. The dominant population in the anammox system was Planctomycetes . Salinity is a feasible factor for controlling the PN/A process.